2009
DOI: 10.14221/ajte.2009v34n5.2
|View full text |Cite
|
Sign up to set email alerts
|

The Attractors of Teaching Biology: a Perspective from a Turkish Context

Abstract: Because the teaching occupation plays a crucial role in a country's development, policymakers and teacher recruitment units all around the world strive to understand how to attract individuals to this profession. However, research regarding the attractors of teaching has been conducted almost entirely in developed countries and has not focused on particular subject areas to be taught. In addition, only limited lists of attractors have been used. Accordingly, the main purpose of this study was to examine what a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…et al (2012), however, did reveal a significant difference between science and non-science students: the former being less positively motivated than the latter. Moreover, Boz and Boz (2008) found that both intrinsic and extrinsic factors influenced the choice to teach among mathematics and chemistry students, and likewise, Kilinc and Mahiroglu (2009) among biology students, while Topkaya and Uztosun (2012) discovered English students were motivated by altruistic and intrinsic reasons. The motivational effect of Expert Career/High Demand beliefs were found to be significant in terms of gender and age, and beliefs in Good Salary significant in relation to subject area.…”
Section: Discussionmentioning
confidence: 99%
“…et al (2012), however, did reveal a significant difference between science and non-science students: the former being less positively motivated than the latter. Moreover, Boz and Boz (2008) found that both intrinsic and extrinsic factors influenced the choice to teach among mathematics and chemistry students, and likewise, Kilinc and Mahiroglu (2009) among biology students, while Topkaya and Uztosun (2012) discovered English students were motivated by altruistic and intrinsic reasons. The motivational effect of Expert Career/High Demand beliefs were found to be significant in terms of gender and age, and beliefs in Good Salary significant in relation to subject area.…”
Section: Discussionmentioning
confidence: 99%
“…Erten (2014) affirmed intrinsic factors. Studies by Kilinc and Mahiroglu (2009); Saban (2003) and Sahin (2010) revealed extrinsic motivations as the highest factors for choosing teaching as a career. Ozsoy et al (2010) found altruistic factors having the highest motivation.…”
Section: The Educational System In Nigeriamentioning
confidence: 99%